Intermittent and continuous energy restriction result in similar weight loss, weight loss maintenance, and body composition changes in a 6 month randomized pilot study. Issue 2 (10th December 2020) - Steger, Felicia L.; Donnelly, Joseph E.; Hull, Holly R.; Li, Xinyang; Hu, Jinxiang; Sullivan, Debra K.
Summary: Poor adherence is a barrier to successful weight control. Intermittent energy restriction (IER) provides an alternative approach to those for whom daily energy restriction is not ideal. This study assessed changes in weight, body composition, and macronutrient intake for an IER and a continuous energy restriction (CONT) approach within a multicomponent weight management intervention. We randomized 35 adults with overweight/obesity (BMI = 31.2 ± 2.4 kg/m 2 ) to CONT or IER for 24 weeks (12‐week weight loss intervention and 12 weeks of weight loss maintenance). Diets were delivered within a multimodal weight management program including weekly group meetings with a registered dietitian, increased physical activity, and a comprehensive lifestyle change program. Retention and adherence were similar for CONT and IER. Weight, BMI, fat mass, percentage body fat, waist circumference, hip circumference, blood pressure, and heart rate all decreased after 24 weeks (all, P  < .01), but there were no main effects of group (all, P  > .27). Weight loss was clinically relevant in both CONT (11.38 ± 7.9%) and IER (9.37 ± 9.7%), and the proportion of each group achieving 5% weight loss was 82 and 61% ( P = .16), respectively. Participant satisfaction was high in both groups. The results from this study (a) support the feasibility of IER as an alternative for weight loss and weight loss maintenance, (b) indicate that IER is an effective alternative to CONT for weight control and improvements in body composition, and (c) emphasize the importance of intensive lifestyle interventions with ongoing support for effective behaviour modification.